2011
DOI: 10.1179/1743281210y.0000000006
|View full text |Cite
|
Sign up to set email alerts
|

Electrovortex field in DC arc steelmaking furnaces with bottom electrode

Abstract: The article is dedicated to the investigation and operation of the electrovortex movement of liquid metal in direct current arc furnace with a bottom electrode under its own electromagnetic field. The physical and mathematical formulations of the processes are given. The algorithm of a solution is developed, and the method and software package for modelling processes in electric steel smelting furnace are chosen. The developed models are tested for adequacy by test problems. The results of electromagnetic fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…The comparison of the obtained results by different software packages and methods showed an insignificant difference of ,3%. [11][12][13][14][15] The similarity of the calculations performed by different methods and software packages confirms the reliability of the methods and significance of the results.…”
Section: Verification Of Obtained Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The comparison of the obtained results by different software packages and methods showed an insignificant difference of ,3%. [11][12][13][14][15] The similarity of the calculations performed by different methods and software packages confirms the reliability of the methods and significance of the results.…”
Section: Verification Of Obtained Resultssupporting
confidence: 61%
“…The results of the calculations show the fact that the Lorentz force in such furnaces is essential for the appearance of EVF. 11,12 The velocity field for isothermal formulation, when the power is insignificant and only compensates losses through the refractory based on the obtained results of electromagnetic force, was calculated in a previous publication. 13 The calculations were carried out in both 2D and 3D formulation.…”
Section: Results Of Solution and Discussionmentioning
confidence: 99%
“…The study done by Wang et al 1,2) indicated that convection and radiation heat transfer mechanisms are responsible for heating and melting iron scrap in the steelmaking process. Kazak et al [3][4][5][6] concluded that the Lorenz force had the major effect on the origination of the vortex motion of a melt in bottom electrode direct current (DC) EAF.…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary analysis provided the optimal division into elements, as well as their form [13][14][15]. The domain area was split into elements unevenly: in the area of the electrodes and boundary with the fettle, where large gradients of all the parameters are situated, the elements were densely located and were of a small size, approximately 0.01 of the electrode radius.…”
Section: A Model Of An Industrial Furnacementioning
confidence: 99%